-9f+5+1=9-10f

Simple and best practice solution for -9f+5+1=9-10f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9f+5+1=9-10f equation:



-9f+5+1=9-10f
We move all terms to the left:
-9f+5+1-(9-10f)=0
We add all the numbers together, and all the variables
-9f-(-10f+9)+5+1=0
We add all the numbers together, and all the variables
-9f-(-10f+9)+6=0
We get rid of parentheses
-9f+10f-9+6=0
We add all the numbers together, and all the variables
f-3=0
We move all terms containing f to the left, all other terms to the right
f=3

You can always share this solution

See similar equations:

| p=p-11 | | -2w+10=2w-10 | | x3=-48 | | -10-2j=-4j+8+8j | | 3c+5=4c-1 | | 2(3k+5)=9k-3(k+4)-1 | | 5x+1+x-9=9x-80 | | -2-5b=-3b | | | | Y=3x-9x-27x | | 4x+34=1-6 | | Y=x2-225 | | 12x+3+7x-2=90 | | 7p/10+9=15 | | 2.5x=5x+3 | | 7r-15=2r+10 | | 11=7t/4 | | (2x-10)=-3 | | 50.50+4x=56.10 | | 3x-6=1x-18 | | 12-222x+34=180 | | 3+-1x=-4 | | (5-3n)=4 | | (2x)+58=180 | | (?11/6)+m=-2/9? | | 3.5g+7=1.5g+15= | | -13=20m+5-2m | | 5x-1+15x+1=25x-25 | | 6.68=??2.3c+0.72.3c+0.7 | | -13=22m | | 3y+4=6y-+19 | | -3(b-15)=12b+30 |

Equations solver categories